Pretty/funny : women comedians and body politics - Mizejewski, Linda (University of Texas Press, 2014)
Women in comedy have traditionally been pegged as either "pretty" or "funny." Attractive actresses with good comic timing, such as Katherine Hepburn, Lucille Ball, and Julia Roberts, have always gotten plum roles as the heroines of romantic comedies and television sitcoms. But fewer women who write and perform their own comedy have become stars, and, most often, they've been successful because they were willing to be funny-looking, from Fanny Brice and Phyllis Diller to Lily Tomlin and Carol Burnett. In this pretty-versus-funny history, women writer-comedians--no matter what they look like--have ended up on the other side of "pretty," enabling them to make it to the top and butt of the joke, the ideal that is exposed as funny